The odd 1s out : the first sequel - Rallison, James (Rallison, James. Odd 1s out (Series), 2020)
"The sequel to the New York Times bestselling The Odd 1s Out, with all new and never-before-seen content featuring opinions, stories, and signature characters from YouTube phenomenon James Rallison. James Rallison has always felt like he was on the outside looking in. His YouTube videos are all about his "odd" behavior, and with over 13 million subscribers and millions more followers on social media, these animations have found their way into the hearts of fans who also feel like a bit of an odd one"--